Pengembangan Kemampuan Kognitif Anak Usia Dini Dalam Mengenal Angka Melaui Media Kartu Angka Bergambar - Debi Ambarwati; Abdul Karim (HMPS PIAUD FTIK IAIN Jember, 2022)
The discussion in the research relates to the planning, implementation and evaluation of teachers in developing cognitive abilities in introducing numbers using picture number cards to group A students at PAUD Permata Jember. This research uses a qualitative research approach with the type of case study research. This research was conducted using observation, interviews, and documentation as data collection techniques. Data analysis uses data condensation, data presentation, and data verification. While the validity of the data using triangulation techniques and data sources. Based on the results of the study, it can be concluded: 1) Teacher planning in developing cognitive abilities in recognizing numbers with illustrated number cards media, namely: Formation of themes, compiling RPPH, preparing learning media, choosing teaching methods and materials to be implemented, and providing information to students before learning activities. 2) The form of teacher implementation in developing cognitive abilities in recognizing numbers with illustrated number cards media, namely: opening activities namely greetings, praying and asking students how they are, Second is the core activity, namely seating management, singing songs about number recognition, distributing illustrated number card media for students, implementation of number recognition, students take turns demonstrating on the blackboard. and then the third is the closing activity, namely the teacher instructs (recalling) the repetition of today's learning activities, and the last is the closing activity of learning (praying). 3) Evaluation of teachers in developing cognitive abilities in recognizing numbers using picture number card media, namely: observation (observation), performance (assignment) and checklist.. Pembahasan dalam penelitian berkaitan dengan perencanaan, pelakasanaan dan evaluasi guru dalam mengembangkan kemampuan kognitif dalam mengenalkan angka dengan media kartu angka bergambar pada peserta didik kelompok A di PAUD Permata Jember. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan jenis penelitian studi kasus. Penelitian ini dilakukan menggunakan observasi, wawancara, dan dokumentasi sebagai teknik pengumpulan data. Analisis data menggunakan kondensasi data, penyajian data, dan verifikasi data. Sedangkan keabsahan data menggunakan triangulasi teknik dan sumber data. Berdasarkan hasil penelitian dapat disimpulkan: 1) Perencanaan guru dalam mengembangkan kemampuan kognitif dalam mengenal angka dengan media kartu angka bergambar, yaitu: Pembentukan tema, menyusun RPPH, menyiapkan media pembelajaran, memilih metode dan bahan ajar yang akan dilaksanakan, serta memberikan informasi pada peserta didik sebelum kegiatan pembelajaran. 2) Bentuk pelaksanaan guru dalam mengembangkan kemampuan kognitif dalam mengenal angka dengan media kartu angka bergambar, yaitu: kegiatan pembukaan yaitu salam, berdo'a dan menanyakan kabar peserta didik, Kedua adalah kegiatan inti yaitu pengelolaan tempat duduk, menyanyikan lagu tentang pengenalan angka, membagikan media kartu angka bergambar pada peserta didik, pelaksanaan pengenalan angka, Peserta didik secara bergantian mendemonstrasikan dipapan tulis. dan selanjutnya ketiga adalah kegiatan penutupyaitu guru menginstruksikan kembali (recalling) pengulangan kegiatan pembelajaran hari ini, dan yang terakhir adalah kegiatan penutup pembelajaran (berdo'a). 3) Evaluasi guru dalam mengembangkan kemampuan kognitif dalam mengenal angka dengan media kartu angka bergambar, yaitu: observasi (pengamatan), unjuk kerja (penugasan) dan checklist.